Cover Image. Issue 13 (29th October 2020) - Dietsch, Craig; Hedrick, Kathryn; Owen, Lewis A.; Caffee, Marc W.
Abstract : The cover image ©Kathryn A. Hedrick is based on the Original Article Tracking denudation and sediment production and transport with cosmogenic 10Be in arid, high‐altitude Himalayan half‐grabens, Zanskar, northern India by Craig Dietsch et al., https://doi.org/10.1002/esp.4954 .